Animation Education Innovation of Big Data in the New Media Environment. (8th March 2022) - Zhang, Lu; Zhang, Zhuoran
Abstract : Animation education is an essential part of art education. Animation education in China started late, and its development was intermittent. After entering the 21st century, animation education has developed at an unreasonably high speed and has formed layers of animation education bubbles. There are many problems and drawbacks behind the rapid development of animation education, but it has been slowly improved and some results have been achieved. In today's multimedia age, the digital revolution has brought a brand new environment and space for contemporary animation, and a large cross-field animation industry is gradually taking shape. China's animation industry should actively respond to the overall innovation of the global animation industry and build a new animation industry development model that adapts to the era of big data. And it builds an animation education system that adapts to the big data environment and continuously supplies talents for the animation industry. This article will study the innovation of animation education based on big data. This article introduces innovative methods of animation education based on big data and designs an animation education platform based on big data. It also conducted a questionnaire survey of learners using the platform based on the Technology Acceptance Model (TAM) and concluded: among the four-dimensional options of TAM, the average proportion of people who choose to agree is 49.5%, and the proportion of people who choose to disagree is 1.81%. This proves that most learners think that the animation learning platform in this article is useful and satisfied with the platform, and only a very small number of people have a poor experience of using the platform.